Prognostic Factors on the Graft-versus-Host Disease-Free and Relapse-Free Survival after Adult Allogeneic Hematopoietic Stem Cell Transplantation - Yao-Chung Liu; Sheng-Hsuan Chien; Nai-Wen Fan; Ming-Hung Hu; Jyh-Pyng Gau; Chia-Jen Liu; Yuan-Bin Yu; Liang-Tsai Hsiao; Tzeon-Jye Chiou; Cheng-Hwai Tzeng; Po-Min Chen; Jin-Hwang Liu (Stem Cells International)
The cure of hematologic disorders by allogeneic hematopoietic stem cell transplantation (HSCT) is often associated with major complications resulting in poor outcome, including graft-versus-host disease (GVHD), relapse, and death. A novel composite endpoint of GVHD-free/relapse-free survival (GRFS) in which events include grades 3-4 acute GVHD, chronic GVHD requiring systemic therapy, relapse, or death is censored to completely characterize the survival without mortality or ongoing morbidity. In this regard, studies attempting to identify the prognostic factors of GRFS are quite scarce. Thus, we reviewed 377 adult patients undergoing allogeneic HSCT between 2003 and 2013. The 1- and 2-year GRFS were 40.8% and 36.5%, respectively, significantly worse than overall survival and disease-free survival (log-rank p<0.001). European Group for Blood and Marrow Transplantation (EBMT) risk score > 2 (p<0.001) and hematologic malignancy (p=0.033) were poor prognostic factors for 1-year GRFS. For 2-year GRFS, EBMT risk score > 2 (p<0.001), being male (p=0.028), and hematologic malignancy (p=0.010) were significant for poor outcome. The events between 1-year GRFS and 2-year GRFS predominantly increased in relapsed patients. With prognostic factors of GRFS, we could evaluate the probability of real recovery following HSCT without ongoing morbidity.